IndOBIS, an ocean biogeographic information system for assessment and conservation of indian ocean biodiversity - Chavan, V.; Achuthankutty, C. T.; Vanden Berghe, E.; Wafar, M. (Indian Journal of Marine Sciences, 2005)
Compilation of inventories of components of coastal and marine biodiversity of Indian Ocean is hampered by several factors: low effort by some countries, preference to certain taxon, dwindling taxonomic expertise, low infrastructure of Information Technology, databases that are scattered and often non-interoperable, inconsistent reporting and a marked reluctance to share data and information. The creation of the Indian Ocean node of the Ocean Biogeographic Information System is meant to overcome some of these constraints. Benefiting from progress in Information Technology and building on the global efforts on understanding what lives in our seas, the IndOBIS aims to grow into a self-sustaining and collectively supported process of information collation, analysis and dissemination, serving the countries of the region and the international scientific community.
Keywords: biodiversity informatics; biogeography; distributed database systems; Indian Ocean; IndOBIS; information systems; Ocean Biogeographic Information System